Histopathological Effects and Element Concentration Of Body Tissues Of Ranid Frog Inhabiting Polluted Water Sites - Zahra, Aqeela; Tayyab, Muhammad; Qureshi, Irfan Zia (European Scientific Journal, ESJ, 2016)
Freshwater or wetlands are being polluted on regular basis due to the release of domestic sewage and most importantly industrial effluents that include chemicals, organic pollutants and heavy metals, and run-off from land-based activities containing leached fertilizers. Pollutants are such substances that reduce quality of water that effect directly and indirectly. The present study was carried out on Korang River Islamabad/Rawalpindi. Two different locations were selected along the Korang River. The data were collected two times during the current study period; March 2012, and October 2012. Ranid frogs (n=10) were captured from all selected sites, which were dissected to collect blood and body tissue samples. During the month of March and October the concentration of heavy metals in water samples increase and decrease significantly at both sites of Korang River. The continuous leaching of contaminants may cause abnormal tissue damage in amphibians making them more vulnerable to predation and competition and also decreased reproductive success.